ANALYSIS OF THE ADVERSE DRUG REACTIONS COLLECTED THROUGH ACTIVE SURVEILLANCE IN THE PHARMACOVIGILANCE UNIT OF A TERTIARY CARE HOSPITAL - Ingale, Anand M; Nadig, Pratibha; Chakraborty, Ananya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of the study were to analyze the various adverse drug reactions (ADRs) collected in the Pharmacovigilance Unit of Vydehi Institute of Medical Sciences and Research Centre with respect to their causality, severity, and preventability and also to identify the various risk factors, concomitant medications, and comorbid conditions with the occurrence of these events. Methods: A prospective, non-interventional, observational, and cross-sectional study was carried out in the various clinical departments of Vydehi Institute of Medical Sciences and Research Centre from June 2014 to May 2015. The Classes of drugs, Organ system involved, Comorbid conditions associated and Concomitant drugs involved in causing ADRs were looked into. The assessment for causality and severity was determined by Naranjo and Modified Hartwig and Siegel scales, respectively. The data were compiled and subjected to descriptive statistical analysis. Results: A total of 433 patients developing ADR reports were analyzed during our study period. Of these, 53.59% were females. 75% of them were of adult age group. Antimicrobials and chemotherapy group showed the maximum ADRs. The skin and appendages (27.6%) were the most affected organ system followed by the gastrointestinal system (22.8%). Comorbid conditions were found in 76 (20.1%) reports; of which diabetes (28.9%) and hypertension (26.3%) were maximum. 74 were serious reports. Maximum reports were probable and of mild severity. Conclusion: Through active surveillance of the ADRs helps in early detection and prevention of all the possible adverse events associated with the usage of drugs and thereby provides a better health-care treatment to the patients. Â 